Improvement of Batik Liquid Waste Quality with IPAL Mini Technology: Case on Flower Tourism Sidomulyo Village in Batu, Indonesia - Siti Asmaul Mustaniroh; Ika Atsari Dewi; Aris Subagiyo; Sisca Fajriani (Universitas Muhammadiyah Sidoarjo, 2021)
Sidomulyo Village, a flower tourist village, in Batu city is one tourist destination in East Java Province based on local wisdom as an icon of Agro-industrial and Agro-tourism in the development of regional tourism. The local products from Sidomulyo Tourism Village include ornamental plants, cut flowers and batik. Sidomulyo Batik UKM is a batik producer with a capacity of 20 sheets per month @ 2.25 m2 and uses manual coloring technology. So far, UKM Batik Sidomulyo has been doing the coloring process in partnership with UKM Batik in Banyuwangi and Trenggalek Regencies due to technological limitations in the processing of batik liquid waste which still contains hazardous and toxic materials so if no action is taken it can damage the ecosystem. One of the strategic solutions is the technology transfer of the mini Wastewater Treatment Plant (WWTP) which utilizes biological waste treatment technology by utilizing bacteria and facilities that are Proven Technology. The mini WWTP installation uses 3 processing rooms including (1) separation of wax content from liquid waste, stirring with coagulant treatment to separate liquid waste from B3 waste and (3) purification of liquid waste by treating biofilter media and anaerobic bacteria. The levels of BOD and COD of the waste will be measured before and after the use of the mini WWTP so that it will be environmentally friendly without reducing the quality of batik as a support for souvenir products typical of Sidomulyo Tourism Village.